The Characteristics and Knowledge of Family of Patients with CKD about AV- Shunt At Dr. Zainoel Abidin General Hospital - Rivai, Mohammad Arif; Junaidi, Fachrul; Khalilullah, Saif Alvin; Muzakkir, Yumna (Journal of International Surgery and Clinical Medicine, 2023)
Introduction: Identifying the CKD progression of the patient should be presented with a range of choices for renal replacement treatment. Therefore, establishing vascular access for hemodialysis is significantly correlated with the survival rate of patients as well as knowledge related to access. Thus, in this study, we aim to report the characteristics and knowledge of the family of patients with CKD about AV-shunt at Dr. Zainoel Abidin General Hospital. Method: This research is descriptive research with a retrospective approach. This study evaluated the "Social Demographic and Medical Character" and "Knowledge towards AV Shunt" family of patients with CKD at RSUD Dr. Zainoel Abidin in Banda Aceh.  The samples in this study were all patients undergoing hemodialysis who had carried out AV-shunt at the hemodialysis installation at RSUD Dr. Zainoel Abidin from July 1 to July 31, 2021.  The data were analyzed descriptively by using SPSS. Results: From 80 respondents, an average age of 50.39 ± 12.594. Most AV Shunt care trainers are from doctors, and the rest are from doctors and nurses (6,3%). Regarding our study, 88,8% of the patients' families received education related to the AV-shunt, and only 11,3% did not. Conclusion: Regarding this study, we can conclude that the patient’s family knows about AV Shunt but must still be evaluated to maintain good AV Shunt function.